Metastasis of mucinous breast carcinoma to the lower alveolus as initial presentation: a diagnostic dilemma - Priyadarshini Guha,; Zachariah Chowdhury, (Autopsy and Case Reports, 2022)
Metastases in the oral cavity are rare and comprise approximately 1% of all oral malignancies. They usually involve the jaws but may also be found in the soft tissues and salivary glands. Women's most common metastatic malignancies are from primary breast cancers. However, metastasis of mucinous breast carcinoma to the lower alveolus mimicking an aggressive primary malignancy as the initial presentation is exceptionally uncommon. We describe the case of a 66-year-old lady with an ulceroproliferative growth in the right lower alveolus. The lesion eroded the mandible and involved the adjacent soft tissues with no prior history of lesion anywhere else. The lesion clinically mimicked a squamous cell carcinoma and masqueraded as a salivary gland mucinous adenocarcinoma on histopathology. The possibility of a metastatic lesion from the breast rather than a primary of the alveolus was also entertained, aided by the immunohistochemical findings of positivity of the tumor cells for GATA3. A positron emission tomography (PET) scan was undertaken to ascertain the primary site. It detected a hypermetabolic lesion in the left breast, which biopsy revealed mucinous breast carcinoma on histopathological evaluation. Metastasis of breast mucinous carcinoma by the hematogenous route is extremely rare; very few cases have been reported. This case illustrates the diagnostic challenges such a lesion can pose to the surgeon and the pathologist. In the advent of such lesions being the initial clinical presentation, a vigilant clinicopathological and radiological assessment is essential to detect the primary.